2021
DOI: 10.1007/s11082-021-02950-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance investigation of spectral-efficient high-speed inter-satellite optical wireless communication link incorporating polarization division multiplexing

Abstract: Space information transmission links are crucial for covering the entire globe for communication purposes. The traditional microwave frequency-based satellite communication links have high latency and low information transmission rates. In the last few years, intersatellite optical wireless communication (IsOWC) technology has evolved significantly as a result of its numerous benefits like wide channel bandwidth, high-speed links, and low mass and power requirements. Different research groups have proposed IsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It is suggested to use higher TADs for the higher-order OAM beams. We considered LG mode profiles with larger differences such as LG00, LG140, and LG400 to realize OAM multiplexing, and it was observed that mode coupling becomes insignificant in these distant mode profiles as compared to the reported research where LG/HG modes with lesser gaps are considered [ 1 , 43 , 44 , 58 ]. We performed an extensive literature survey and found that the highest capacity that has been reported so far in OSC is 4 [ 44 ], 3.84 [ 61 ], 1.6 Tbps [ 62 ], and 320 Gbps [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested to use higher TADs for the higher-order OAM beams. We considered LG mode profiles with larger differences such as LG00, LG140, and LG400 to realize OAM multiplexing, and it was observed that mode coupling becomes insignificant in these distant mode profiles as compared to the reported research where LG/HG modes with lesser gaps are considered [ 1 , 43 , 44 , 58 ]. We performed an extensive literature survey and found that the highest capacity that has been reported so far in OSC is 4 [ 44 ], 3.84 [ 61 ], 1.6 Tbps [ 62 ], and 320 Gbps [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…For OSC systems, single polarization QAM [ 57 ] and dual polarization QAM with different variants such as 4-QAM [ 37 ], 16-QAM [ 58 ], 64-QAM [ 59 ], and 128-QAM [ 60 ] have been reported several times and revealed that bandwidth efficiency of higher QAMs is better than conventional QPSK, DPSK, etc. modulations.…”
Section: Simulation Design Of Proposed Pdm-256-qam Modulated Oam-osc ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 31 have analyzed the performance of fixed and variable gain relays in dual‐hop RF‐FSO systems and considered a subcarrier intensity modulated system. Mode division multiplexing and polarization division multiplexing‐based FSO systems for inter‐satellite communication were proposed in previous studies 32,33 . The practical implementation of m‐QAM and m‐PSK‐based FSO systems was studied with 650 and 850 nm wavelengths 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Mode division multiplexing and polarization division multiplexing-based FSO systems for inter-satellite communication were proposed in previous studies. 32,33 The practical…”
Section: Introductionmentioning
confidence: 99%